ACCOUNTING IN THE CONTEXT OF THE MODERN DEVELOPMENT OF THE DIGITAL ECONOMY (INNOVATIVE ECONOMY, 2022)
Shmyhel O.Ye. ACCOUNTING IN THE CONTEXT OF THE MODERN DEVELOPMENT OF THE DIGITAL ECONOMYPurpose. The aim of the article is to substantiate the need for the development of digitalization of modern accounting and financial reporting.Methodology of research. The study was conducted using a dialectical approach to the study of the current state of development of the digital economy. General scientific and special methods were used, in particular: analytical - when reviewing normative sources; monographic - when studying literary sources on issues of digital economy and accounting; system and analytical method - when processing the received information.Findings. It was determined that in the conditions of digitization of business processes, introduction and development of new business concepts, approaches to reporting methodology are changing, the need to create a new accounting concept is increasing. It is substantiated that digitalization contributes to the change in the functioning of management services and their responsibilities in all divisions of the business entity, and in the accounting department, in particular.It was revealed that the result of the development of digital technologies will be the transformation of the organizational structure and management services of the accounting department, including due to the reduction of the staff and the review of the functionality, the introduction of new technologies for processing primary documents and information, the modernization of accounting processes and accounting policy in general; strengthening requirements for professional skills of users.Origination. Directions for the development of digitalization of the organizational structure of the company’s accounting service are proposed in the article. The introduction of a single electronic data exchange format for financial reporting as a strategic tool for accounting harmonization is substantiated.Practical value. The obtained results of the research will contribute to increasing the efficiency of the formation and development of accounting in the conditions of the digital economy and will become the basis for further scientific developments in this field.Key words: digitalization, information technologies, accounting, financial reporting, digital accounting, digital technologies, business process.
Keywords: digitalization; information technologies; accounting; financial reporting; digital accounting; digital technologies; business process